USE OF COLOR IN MATHEMATICAL TEXT, AS AN AUXILIARY MEANS OF IMPROVEMENT DEMONSTRATION OF LOGICAL TRANSITIONS OF ITS CONTENT - Григулич, Світлана; Щекань, Надія (Modern engineering and innovative technologies, 2024)
The authors emphasize the importance of using auxiliary educational materials, where the mathematical logical steps in theoretical explanations or solving problems are additionally highlighted in color. This form of presentation of educational material ca